Brushing Effect on the Properties of Glass Ionomer Cement Modified by Hydroxyapatite Nanoparticles or by Bioactive Glasses - Rafael A. Martins; Luana M. Marti; Ana C. B. Mendes; Camila Fragelli; Mario Cilense; Angela C. C. Zuanon (International Journal of Dentistry)
This study evaluated the physical and mechanical properties of glass ionomer cement (GIC) associated with 5% hydroxyapatite nanoparticles (NPHAps) and 10% bioactive glass (BAG) 45S5 before and after brushing at different storage times. Surface roughness was evaluated using a rugosimeter, Vickers hardness using a microdurometer, and mass variation measured in an analytical balance at 1, 7, 15, 30, and 60 days before and after the brushing test, with the aid of toothbrushing simulator and soft bristle toothbrushes. Nonnormal distribution was observed, and the nonparametric Wilcoxon and Kruskal–Wallis tests followed by Dunn’s were performed, with a significance level of 5%. We observed higher values for mass loss on the first day for all groups. The surface roughness was lower in the control and NP groups, 30 days after brushing. Higher values for hardness were found in the control group and lower ones for NP, after brushing. The control and BAG groups presented a decrease in hardness over time. The NP group presented the highest values before brushing, while the control group had the highest values after brushing. The association of NPHPa with the GIC is the most promising combination, since it presented satisfactory values for surface hardness. However, conventional GIC not associated with NPHPa or BAG is still an option, since it is available in the market and the most economically viable option.